2020
DOI: 10.3390/cells9122693
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Acid Ceramidase to Improve the Radiosensitivity of Rectal Cancer

Abstract: Previous work utilizing proteomic and immunohistochemical analyses has identified that high levels of acid ceramidase (AC) expression confers a poorer response to neoadjuvant treatment in locally advanced rectal cancer. We aimed to assess the radiosensitising effect of biological and pharmacological manipulation of AC and elucidate the underlying mechanism. AC manipulation in three colorectal cancer cell lines (HT29, HCT116 and LIM1215) was achieved using siRNA and plasmid overexpression. Carmofur and a novel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…A research group demonstrated the therapeutic potential of inhibiting aCDase to counteract critical growth periods in aggressive, chemo-resistant forms of prostate cancer [196]. Increased aCDase activity has also been linked to radiotherapy failure and relapse due to radiation-induced transactivation by activator protein 1 [197,198]. Inhibiting aCDase led to increased cellular radiosensitivity, which resulted in poly-ADP ribose polymerase-1 cleavage and apoptosis through a p53-dependent pathway [198].…”
Section: Ceramide Metabolismmentioning
confidence: 99%
See 2 more Smart Citations
“…A research group demonstrated the therapeutic potential of inhibiting aCDase to counteract critical growth periods in aggressive, chemo-resistant forms of prostate cancer [196]. Increased aCDase activity has also been linked to radiotherapy failure and relapse due to radiation-induced transactivation by activator protein 1 [197,198]. Inhibiting aCDase led to increased cellular radiosensitivity, which resulted in poly-ADP ribose polymerase-1 cleavage and apoptosis through a p53-dependent pathway [198].…”
Section: Ceramide Metabolismmentioning
confidence: 99%
“…Increased aCDase activity has also been linked to radiotherapy failure and relapse due to radiation-induced transactivation by activator protein 1 [197,198]. Inhibiting aCDase led to increased cellular radiosensitivity, which resulted in poly-ADP ribose polymerase-1 cleavage and apoptosis through a p53-dependent pathway [198]. aCDase is becoming an increasingly popular therapeutic target for various cancers to impair tumor progression and relapse [197][198][199][200][201].…”
Section: Ceramide Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…These results may be due to the high adaptive capacity of melanoma cells. However, inhibition of ASAH1 with siRNA or pharmacologically with LCL521 in colorectal cancer cell lines (HT29, HCT116 and LIM1215) enhanced X-ray radiosensitivity [ 139 ]. Moreover, tamoxifen has shown its ability to inhibit ASAH1 in polyploid giant cancer cells by reducing their division [ 140 ].…”
Section: Enzymes Of Ceramide Metabolismmentioning
confidence: 99%
“…RC can be treated by surgery, radiotherapy, chemotherapy, molecular targeted therapy, etc. [ 5 – 8 ]. Clinically, surgical resection is still the primary means for it.…”
Section: Introductionmentioning
confidence: 99%